Effect of Organic Selenium on Testosterone Level and Testes Wight of Broiler Breeder Males (Journal of Hama University, 2024)
The research aim is studying the effect of using organic selenium (OH-SeMet) as a feed additive on the performance reproductive system of broiler breeder males. For this study, 50 birds (broiler breeder males / Ross 308 strain) were used for this study, at the age of 17-30 weeks. The birds were distributed randomly into two groups, the first group was considered experimental group (A) consisting of 25 roosters, and the nutritional needs were given according to the recommendations of the company producing Ross 308 strain in addition to organic selenium (OH-SeMet) at a dose of 300 mg/ton as a feed additive. As for the second group (B), it was considered a control group (control) consisting of 25 roosters, and this group was provided with nutritional needs according to the recommendations of the company producing Ross 308 strain. Blood samples were taken once from the pterygoid vein at the age (30) weeks, in order to determine the testosterone (Te) level in plasma, then the testes were removed after slaughter to measure the weight of the testes, and the results showed that a high Significant level of testosterone in the blood plasma with a significant increase in the weight of the testes. The results showed the possibility of using organic selenium to improve the level of testosterone and the weight of testes in broiler breeder males, by comparing the levels of the male hormone (Te) in blood plasma between the two groups that were given organic selenium and those that were not given it, and the best results were recorded in the first group that was given selenium Organic (OH-SeMet) as a feed additive at a concentration of 300 mg/ton.
Keywords: Organic Selenium - Broiler Breeder Males – Rooster – Testosterone – Testes – Feed additive.